2013
DOI: 10.1016/j.steroids.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of the polycystic ovary syndrome phenotype

Abstract: The etiology of the polycystic ovary syndrome (PCOS) remains unclear, despite its high prevalence among infertility disorders in women of reproductive age. Although there is evidence for a genetic component of the disorder, other causes, such as prenatal insults are considered among the potential factors that may contribute to the development of the syndrome. Over the past few decades, several animal models have been developed in an attempt to understand the potential contribution of exposure to excess steroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 83 publications
1
90
0
3
Order By: Relevance
“…In agreement with our results, previous studies have reported disrupted hormonal profile in PCOS animal models, compared to controls [33]. Evidence for endocrine changes in PCOS animal models is inconsistent, indicating the differences may be due to various factors, including type of hormone administered, time of hormone exposure, age of animal during the time of study, different PCOS phenotypes in animal models and time of sampling [21,[33][34][35].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with our results, previous studies have reported disrupted hormonal profile in PCOS animal models, compared to controls [33]. Evidence for endocrine changes in PCOS animal models is inconsistent, indicating the differences may be due to various factors, including type of hormone administered, time of hormone exposure, age of animal during the time of study, different PCOS phenotypes in animal models and time of sampling [21,[33][34][35].…”
Section: Discussionsupporting
confidence: 90%
“…These animals exhibit elevated LH pulse frequency and irregular reproductive cycles, which may result from a number of mechanisms, including alterations in synaptic input to GnRH neurons, 2004, desensitization of GnRH neurons to steroid feedback, increased amplitude/frequency of GnRH pulses, and increased gonadotropic sensitivity to the GnRH stimulation [20][21][22][23][24]. Kisspeptin, an essential gatekeeper of puberty onset and GnRH secretion, mediates steroid feedback and metabolic cues during different developmental stages throughout the lifespan [9,25].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, prenatal exposure to testosterone is known to cause polycystic ovarian syndrome (PCOS) in adult females as evidenced by increased follicle recruitment, disrupted cyclicity, and high estradiol secretion (Padmanabhan and Veiga-Lopez 2013). When pregnant ewes were exposed to high levels of androgens beginning at day 30 of gestation, the female offspring develop a PCOS phenotype as adults.…”
Section: Mirna In Ovarian Developmentmentioning
confidence: 99%
“…Pode-se induzir o aparecimento de fenótipos similares à SOP com exposição a esteroides sexuais (22,23), letrozol (24), luz contínua (25), entre outros (26). Espécies tais como primatas, ovelhas, ratos e camundongos tem sido utilizados como modelos animais de SOP (27). Porém, o uso de primatas e ovelhas para pesquisa é extremamente caro (22,28).…”
Section: Modelos Animais Para O Estudo Da Síndrome Dos Ovários Policíunclassified
“…Diversos estudos tem utilizado a exposição a esteroides sexuais no período pré-natal, neonatal ou pré-puberal (27). Em ratas, foi mostrado que a exposição pré-puberal à dihidrotestosterona (DHT), que é um androgênio não aromatizável, induz a características metabólicas e reprodutivas similares à SOP na vida adulta desses animais (22 Há diversas diferenças fisiológicas dos adipócitos subcutâneos para os viscerais, especialmente em transporte e armazenamento de ácidos graxos, lipólise, produção de adipocinas e adaptação ao balanço energético positivo e negativo (36).…”
Section: Modelos Animais Para O Estudo Da Síndrome Dos Ovários Policíunclassified